Timely diagnosis of dementia? Family carers' experiences in 5 European countries - Woods, Bob; Arosio, Francesca; Diaz, Ana; Gove, Dianne; Holmerová, Iva; Kinnaird, Lindsay; Mátlová, Martina; Okkonen, Eila; Possenti, Mario; Roberts, Jennifer; Salmi, Anna; van den Buuse, Susanne; et al. (International journal of geriatric psychiatry, 2019)
OBJECTIVES: Timely diagnosis of dementia is recommended in national strategies. To what extent is it occurring across Europe, what factors are associated with it, and what is the impact on carers emotions of quality of diagnostic disclosure? METHODS/DESIGN: Survey of family carers recruited through 5 Alzheimer's associations (Czech Republic, Finland, Italy, the Netherlands, and Scotland). One thousand four hundred and nine carers participated, 84% completing online. Fifty-two percent were adult children, and 37% were spouses, with median age 57. Most (83%) were female. RESULTS: Nearly half (47%) of carers reported that an earlier diagnosis would have been preferable. Delaying factors included reluctance of the person with dementia, lack of awareness of dementia, the response of professionals, and delays within health systems. Recent diagnoses were no more likely to be considered timely, although professional responses appeared to be improving. Delayed diagnoses were more often reported by adult child carers and where the diagnosis was made in the later stages of dementia, or another condition had been previously diagnosed. In all countries except Italy, the diagnosis was shared with the person with dementia in the majority of cases. Timely diagnoses and higher quality diagnostic disclosure are associated with better adjustment and less negative emotional impact on carers in the short and medium term. CONCLUSIONS: Although the study sample were well educated and likely to be in touch with an Alzheimer organisation, many continued to experience the diagnosis of dementia as coming too late, and further work on public awareness, as well as on professional responses, is needed.
Keywords: family carers; Male; Evropa; lidé středního věku; timely diagnosis; Awareness; Europe; osoby pečující o pacienty; Professional Competence; manželé; Humans; uvědomování si; Middle Aged; senioři; mužské pohlaví; Female; Early Diagnosis; Delivery of Health Care; Aged; ženské pohlaví; Dementia; Health Services Research; Adult; adjustment; demence; diagnostic disclosure; poskytování zdravotní péče; odborná způsobilost; Caregivers; výzkum zdravotnických služeb; časná diagnóza; Alzheimer's; dospělí; lidé; Spouses; dementia